Foot Physical Activity Can Reduce Blood Pressure In Hypertension To Eldery - Praditya G; Kartikasari A; Widyastuti Y; Rahmasari I (Proceeding of International Conference on Science, Health, And Technology, 2021)
Hypertension is a systolic blood pressure of 140 mmHg or more and a diastolic blood pressure of 90 mmHg or more. As the elderly get older there will be physical changes in the cardiovascular system, namely the heart valves are thickened and stiff, the ability to pump blood decreases (decreased contraction and volume), decreased elasticity of blood vessels, and increased resistance of peripheral blood vessels, so that blood pressure increases and causes hypertension in the elderly. Hypertension can be overcome with pharmacological and non-pharmacological therapies, one example of non-pharmacological therapy, namely physical activity on foot, physical activity on foot is a routine activity that uses the power of the leg muscles to perform movements alternately, for 30 minutes per day. Objective: to determine the effect of physical activity on foot for the elderly with hypertension to reduce blood pressure. The method in this research is quantitative with research design pre-experimental with one group pre-test and post-test design. The sample of this study was 18 elderly with hypertension by observing the research subjects. Blood pressure measurements were measured with a sphygnomater and stethoscope and then recorded before and after physical activity on foot. Measurement of systolic and diastolic blood pressure before walking physical activity was 140/90 mmHg and 150/100 mmHg, while systolic and diastolic blood pressure after walking was 120/80 mmHg and 140/90 mmHg. The conclusion of this study is that physical activity on foot can lower blood pressure and can be used as a non-pharmacological therapy for elderly patients with hypertension.